AB0538 TNFAIP3 RS675520 variant may predict response to rituximab treatment in rheumatoid arthritis. (23rd January 2014) - Guseva, I.; Soroka, N.; Devyataykina, A.; Lukina, G.; Aleksandrova, E.; Novikov, A.; Glukhova, S.; Trofimov, D.; Nasonov, E.
Abstract : Background: Individual response to biological treatment is highly variable and potentially subject to genetics influence. There is a need for biomarkers that are able to predict clinical response to rituximab (RTX) treatment. Objectives: To examine whether there are genetic polymorphisms associated with response to RTX therapy. Methods: 53 RA patients receiving RTX therapy were included in this pharmacogenetic prospective study (mean age 51±15 years and mean disease duration 8.2±6.2 years). Response to RTX therapy was evaluated using the EULAR criteria (DAS28-ESR) at 6 months after the first RTX course (two intravenous infusions at weeks 0 and 2). The following gene polymorphisms (SNPs) were genotyped: IL-6 (rs1800795), IL-6RA (rs8192284), TNFA (rs1800629), TNFAIP3 (rs675520, rs6920220, rs10499194), MCP-1/CCL2 (rs1024611), CTLA4 (rs3087243), PTPN22 (rs2476601). Comparison of responses for the following groups (good responders vs moderate/non responders, and good responders vs moderate responders) was evaluated using logistic regression, and the results were expressed as ORs with 95% CI. Results: After the 1st RTX course a good response was achieved in 18 (40, 0%) patients. 29 (54, 7%) patients were defined as moderate responders and 6 (11, 3%) patients as non-responders. A SNP at TNFAIP3 locus (rs675520) tended to be associated with the response to RTX treatment in both groups of responders vs moderate/non responders (OR 4, 6, 95% CI 0, 9-23, 6, p=0, 06) and responders vs moderate responders (OR 4, 8, 95% CI 0, 9-25, 5, p=0, 062). The patients with homozygous genotype CC had the worse results than patients with CT and TT genotypes in the swollen joint count (p=0, 036), tender joint count (p=0, 034), DAS28 (p=0, 01) and HAQ (p=0, 01) at 6 months after the first course of treatment. No evidence for association was detected at the other SNPs tested Conclusions: Our preliminary results suggest the TNFAIP3 SNP (rs675520) may possibly influence the response to RTX therapy. This finding requires replication in additional patients groups. Disclosure of Interest: None Declared